A COMPREHENSIVE INVESTIGATION INTO THE DEVELOPMENT OF A DEEP LEARNING MODEL FOR ROBUST CLASSIFICATION IN THYROID DISEASE DIAGNOSIS - Chaphekar, Minal; Chandrakar, Omprakash (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In recent years, the emerging field of deep learning has attracted widespread attention, especially in its application to the detection of thyroid nodules, aiming to distinguish between benign and malignant cases. However, the lack of sufficient clinical images has posed a significant hurdle, hindering the development of effective deep learning models. This research introduces a pioneering deep learning-based characterization framework explicitly designed to address the challenge of detecting malignancy in thyroid nodules from healthcare medical images.The methodology used in this paper focuses on the use of convolutional neural networks. By improving the capabilities of CNNs, a powerful class of deep learning algorithms specifically designed for image processing, our study aims to improve the accuracy and efficiency of the diagnostic process for thyroid disease.The CNN method enables automated extraction of complex patterns and features from thyroid images, providing a robust framework for detecting and classifying thyroid abnormalities. This approach represents an important step forward in the use of advanced computational techniques to improve the efficiency of clinical diagnosis, especially in the thyroid diagnostic domain. The proposed deep learning framework not only represents architectural convergence but also makes significant improvements in overcoming data limitations in thyroid nodule detection. The integration of multi-level transfer learning enriches the model from different data sources, improving its ability to adapt to the complex features inherent in thyroid ultrasound images. Our findings highlight the potential of this approach to revolutionize diagnostic tools for thyroid nodules, meeting a critical need in the field of clinical imaging and diagnosis for more accurate and reliable Provides solutions. This research contributes to the broader landscape of deep learning in clinical diagnosis, pushing the boundaries of innovation and paving the way for improved diagnostic accuracy in the microscopic field of thyroid nodule characterization.